Lingkungan Kerja pada PT. Anugrah Wijaya Maskot - Alfin Adam; Tini Kartini (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
The work environment plays a strategic role in supporting employee effectiveness and organizational sustainability, particularly in creative industry enterprises. This study addresses the main problem of suboptimal work environment conditions at PT Anugrah Wijaya Maskot, which are suspected to affect employee performance and the stability of company revenue. The purpose of this research is to analyze the physical and non-physical work environment conditions and their implications for employee work effectiveness. This study employed a descriptive qualitative approach. Data were collected through direct observation, in-depth interviews, discussions with company personnel, and analysis of internal company documents during fieldwork activities. The findings reveal that the physical work environment has not been optimally managed, especially regarding the availability and feasibility of production facilities, temperature control, and air circulation, which tend to reduce employee comfort and work concentration. Conversely, the non-physical work environment shows relatively favorable conditions, characterized by harmonious working relationships, effective communication, and a supportive social climate among employees. This imbalance between physical and non-physical work environment aspects contributes to fluctuations in operational performance, as reflected in the company’s revenue achievement throughout 2024. These findings highlight the importance of integrated work environment management as a strategic effort to enhance employee productivity and support sustainable organizational performance.